Alfabetização e letramento através do gênero textual história em quadrinhos - MATOS, Maria Tereza de (2022)
At present, the debates about the new methodologies of teaching learning of reading and writing have gained space in educational environments and outside of it, in front of that this research comes to analyze the process of literacy and literacy through a project developed in the Municipal School of Education Infantile and Fundamental Castelinho do Pequeno Príncipe de Novo Repartimento - PA. The objective of the research is to evaluate the contribution of the use of the textual genre Comic in the literacy and literacy of the students of the 3rd year of Elementary School. In this way, positive results were obtained: awakening for reading and writing, social interaction, joy, affectivity, as it awakened in the students the motivation for the classes by means of the reading of several texts in Comics, arranged in printed, among others, elevating them to the best development of reading and writing.